Seroprevalence of hepatitis C virus among patients at a tertiary health care centre in Rajasthan, India - Mathur, Ajay; Goyal, Laxmi Kant; Sharma, Manoj Kumar; Gupta, Arvind Kumar; Hooja, Nupur; Yadav, R. N. (International Journal of Advances in Medicine, 2020)
Background: To ascertain the prevalence of Hepatitis C infection among patients visiting a tertiary care center in Jaipur, Rajasthan. Methods: An observation analytic study was done at a tertiary care center affiliated to Medical College with retrospective analysis of the hospital data of two calendar years. During this period HCV infection screening (anti-HCV) was offered to every suspected patient admitted in hospital and every pregnant women visiting antenatal care clinic. Results: The study prevalence of HCV infection was 0.05% (13/25311). The prevalence was more in female (0.03%) than male (0.02%). The study prevalence of anti-HCV among pregnant female was 0.02% (3/16224). Maximum positive cases (4/13, 30.77% positive cases) were in the age group of 21-30 years (sexually active group) and >50 years age group while minimum positivity was found in children (00 case, 0-20 years age). Conclusions: In this study, prevalence of HCV infection was 0.05%. The study prevalence of HCV among pregnant females was 0.02%. Maximum positive cases (4/13, 30.77% positive cases) were in the age group of >50 years and 21-30 years. This study aids in view to strengthen proper screening for HCV infection to reduce HCV related morbidity and mortality